"Homo poeticus" - edukacyjne wyzwanie, dydaktyczne transgresje = "Homo poeticus" - educational challenge, transgressive teaching - Badnarkowa, Wiga (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
My focus of interest is the child`s (human) ability to conceptualize the content carried by verse (poetry). As literary education starts at the early stage of elementary education, I will present the results of my own pilot study related to reading comprehension of individual words and the ability to combine them into larger, syntactically motivated units.
Keywords: konceptualizacja; kreatywność; edukacja literacka; conceptualization; verbal language; creativity; literary education